Bioinspired Hollow Nanoreactor: Catalysts that Carry Gaseous Hydrogen for Enhanced Gas‐Liquid‐Solid Three‐Phase Hydrogenation Reactions. Issue 2 (11th December 2019) - Li, Zhaohua; Zhu, Zhongpeng; Cao, Changyan; Jiang, Lei; Song, Weiguo
Abstract: For conventional gas‐liquid‐solid three‐phase heterogeneous hydrogenation reactions, hydrogen must be dissolved into the solvent to be a participating reactant, restricting the reaction rates. In this study, we demonstrate that gaseous hydrogen could be directly involved in gas‐liquid‐solid hydrogenation reactions through a bioinspired hollow nanoreactor with superaerophilic surface to enhance the reaction rates. We produce Pd@meso‐SiO2 hollow nanoreactor, whose external surface is modified with perfluorodecyltriethoxysilane (PFDTS). In aqueous solutions, H2 gas could be spread quickly on the surface and stored in the cavity of hollow spheres, and participated in hydrogenation reactions, thereby enhancing H2 concentration around Pd nanoparticles. In hydrogenation of olefin reactions, such three‐phase interface allows rapid and direct transportation of H2 bubbles to the surface of Pd nanoparticles rather than through diffusion of dissolved H2 in liquid phase, leading to an enhanced catalytic rate. This strategy is expected to be useful for designing and developing new catalytic systems of gas‐liquid‐solid three‐phase reaction. Abstract : Bioinspired hollow nanoreactor : The catalytic rate of matched gas‐liquid‐solid three‐phase hydrogenation reactions could be enhanced through a bioinspired hollow nanoreactor with superaerophilic surface to rapidly and directly transfer gas bubbles to the active sites, and thereby enhancing the gas concentration for the interface reaction.